Searching for an invisibly decaying Higgs boson in e+e-, eγ, and γγ collisions - Éboli, O. J P; Gonzalez-Garcia, M. C.; Lopez-Fernandez, A.; Novaes, Sérgio Ferraz [UNESP]; Valle, J. W F (Elsevier B.V., 1994)
Higgs bosons can have a substantial invisible branching ratio in many extensions of the Standard Model, such as models where the Higgs bosons decay predominantly into light or massless weakly interacting Goldstone bosons. In this work, we examine the production mechanisms and backgrounds for invisibly decaying Higgs bosons at the Next Linear e+e- Collider operating in the modes e+e-, eγ, and γγ. We demonstrate that such machine is much more efficient to survey for invisibly decaying Higgs bosons than the Large Hadron Collider at CERN.